Structure of the protein core of translation initiation factor 2 in apo, GTP‐bound and GDP‐bound forms. (21st May 2013) - Simonetti, Angelita; Marzi, Stefano; Fabbretti, Attilio; Hazemann, Isabelle; Jenner, Lasse; Urzhumtsev, Alexandre; Gualerzi, Claudio O.; Klaholz, Bruno P.
<x xml:space="preserve">Abstract</x> Translation initiation factor 2 (IF2) is involved in the early steps of bacterial protein synthesis. It promotes the stabilization of the initiator tRNA on the 30S initiation complex (IC) and triggers GTP hydrolysis upon ribosomal subunit joining. While the structure of an archaeal homologue (a/eIF5B) is known, there are significant sequence and functional differences in eubacterial IF2, while the trimeric eukaryotic IF2 is completely unrelated. Here, the crystal structure of the apo IF2 protein core from Thermus thermophilus has been determined by MAD phasing and the structures of GTP and GDP complexes were also obtained. The IF2–GTP complex was trapped by soaking with GTP in the cryoprotectant. The structures revealed conformational changes of the protein upon nucleotide binding, in particular in the P‐loop region, which extend to the functionally relevant switch II region. The latter carries a catalytically important and conserved histidine residue which is observed in different conformations in the GTP and GDP complexes. Overall, this work provides the first crystal structure of a eubacterial IF2 and suggests that activation of GTP hydrolysis may occur by a conformational repositioning of the histidine residue.